Google sites in education - Abd Wahab, Farhah; Nasri, Nur Izzah; Kamarudin, Nurulhuda (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
This paper aims to make a review on the existing literatures of Google Site’s features and its benefits on teaching and learning process in the classroom. Google Sites is the easiest way to get a quick and up to-date access of data and information online. People can work together on a Site to add file attachments, act as cloud file storage, deliver informations from other Google applications (like Google Drive, Google Calendar, Picasa and Youtube), and new free-form content. It is a platform where creating an educational site together is as easy as editing a document and publish Sites to the world. The Google Sites web application can be access from any Internet connected devices. On the other hand, Google Sites is an educational tool that provides teachers with some theoretical and practical ideas on how to use it in the classroom with students as they can use it as a discussion board, posting homeworks and assignments as well as creating webpages to include course materials. Through all the literature reviews, the findings of this conceptual paper revealed that teachers and students perceive Google Sites as an interactive learning tools that can be integrated in the classroom to assist them in the teaching and learning process.